Sexual health among Kenyan male sex workers in a time of COVID-19. (February 2021) - Macharia, Pascal; Moore, Samantha; Mathenge, John; Ndunda, Erastus; Lazarus, Lisa; McKinnon, Lyle R; Lorway, Robert
Objective: This report identifies the profound effects that the COVID-19 pandemic and the resultant government lockdown have had on sexual health services delivery to a community of marginalised male sex workers in Nairobi, Kenya. Methods: Based on the experiences shared during ongoing virtual conversations with peer health workers, a case study was developed to identify the challenges encountered by peer health workers. Findings: Peer health workers confronted the new health crisis surrounding COVID-19 while also persisting in their efforts to deliver HIV services to male sex workers. Unable to receive status as 'essential workers', their actions often fell short in efforts to maintain male sex workers' access to vital HIV prevention, treatment and care resources. Conclusion: The struggles encountered, amid dwindling resources, underscore the vital work needed to meet the health needs of a marginalised group that remains largely excluded from the government health system.